Partial genes expression assessment of two-component regulation system ArlR and SigB towards Staphylococcus aureus survival in vitro - Nik Ibrahim, Nik Khairul Azizi; Shamsudin, Mariana Nor; Neela, Vasantha Kumari; Sekawi, Zamberi (Academic Journals, 2011)
The current research trend for a new drug development was expanded by using the proteomic approaches. However, the expression on those drug target must be well identified before taking part into proteomics study. One of the most commonly use protocol is the expression profiles on those selected genes during certain simulated conditions. Staphylococcus aureus has been blessed with several virulence factors whichare essential for its pathogenicity. One of the most well studied systems is the Two-Component Regulatory Systems (TCRSs). The TCRSs play a vital role in S. aureussurvival and it become a good candidate for the specific drug target. Prior to determining the role, this study was made to observe the expression pattern of 2 TCRS’ regulatory genes during the treatment with antibiotics against two strains of S. aureus; the Methicillin Susceptible S. aureus (MSSA) and Methicillin Resistant S. aureus (MRSA). The partial transcripted analysis of the reverse transcriptase PCR (RT-PCR) data shows that the rates of expression in selected TCRS genes were different in both strains. Knowing the importance to S. aureus growth and pathogenesis, the TCRS genes can be a good candidate for designing a novel specific drug target against S. aureus especially the MRSA.